LECTURERS’ PERCEPTIONS TOWARD ONLINE TEACHING AND LEARNING DURING CORONAVIRUS DISEASE-2019 AT UNIVERSITY OF LIMPOPO, SOUTH AFRICA - Witness Maluleke; Rivoningo Nyiko (CV. RADJA PUBLIKA, 2024)
The outbreak of Coronavirus Disease-2019 (COVID-19) brought some changes in the Department of Higher Education and Training (DHET), whereby South African Higher Education Institutions (HEIs) had to quickly transition to online Teaching and Learning (T & L). The implementation of online T & L specifically in Historically Disadvantaged Institutions (HDIs) was accompanied by advantages and disadvantages. Many research studies investigate students' perspectives on online T & L, however, there are notable gaps in research concerning lecturers' perceptions on online T & L during COVID-19. Therefore, the aim of this study was to explore lecturers’ perceptions toward online T & L during COVID-19 at University of Limpopo (UL), South Africa. A qualitative research approach was adopted to gather perceptions on this subject, using the permanent staff members attached to the Department of Criminology and Criminal Justice as a case study. This qualitative study employed an exploratory research design due to the limited literature in this area, non-probability purposive sampling was used to select 10 participants. Data was collected using semi-structured Key Informant Interviews (KIIs) conducted by Google Forms and 9 out of the 10 participants completed the interview questions. Inductive Thematic Content Analysis (TCA) was applied to analyse the qualitative data. The results of the study showcase that the online examinations challenges such as students cheating or committing academic misconduct were encountered by the university. The study recommends the university should invest in reliable online proctoring tools that can minimise the manipulation of the assessments offered. Clear policies and guidelines were recommended to maintain online T & L integrity and lastly, the researchers recommend academic workshops that can teach students about the importance of the rules of the examinations and severe punishment if the rules are violated. Overall, the study highlights the value of online T & L and the necessity for ongoing adaptation and support.